The effectiveness of mindfulness training on social adjustment, self-esteem, and hope among transgender individuals in Tehran - Sepideh Savafi; Saeideh Bazzazian; Cesare R Sirtori (Journal of Neurology, Neurological Science and Disorders - Peertechz Publications, 2024)
Introduction: This study aimed to assess the efficacy of mindfulness training in enhancing social adjustment, self-esteem, and hope in transgender individuals.  Methodology: This research employed a quasi-experimental design, incorporating pre-test and post-test measures, along with a control group. The study population comprised transgender individuals receiving support from one of the social support centres under the auspices of the Tehran Municipality in the year 1401 (2022). Fourteen participants from this population were selected using convenience sampling and randomly assigned to two groups: an experimental group and a control group. The experimental group underwent eight sessions of mindfulness training. Subsequently, during the post-test phase, both groups completed questionnaires. Data analysis involved multivariate and univariate analysis of covariance.  Results: The research findings revealed a statistically significant difference in mean scores of social adjustment, self-esteem, and hope between the control and experimental groups during the post-test phase. Mindfulness training contributed significantly to elevating the levels of these variables within the experimental group (p < 0.05).  Conclusion: In light of the research outcomes, mindfulness training emerges as a promising intervention for positively influencing social adjustment, self-esteem, and hope among transgender individuals. Consequently, this educational program is recommended for the provision of psychological services within the target community.